An Analysis of Market Concentration on Selected Food Manufacturing Industry in Malaysia - Kong, Chee Sing (2004)
The Malaysian food manufacturing industry is an important industry in terms of its contribution to manufacturing output, growth and profitability in the food sector. One of the most influential approaches among various theories of industrial organisation is the Structure-Conduct-Performance (S-C-P) model, which highlights the competitive conditions in an industry by examining the structure of the industry related to the behaviour and performance of firms. The elements that constitute market structure and the manner in which it affects firms7 performance and conduct are important aspects to consider in understanding the S-C-P relationships. This study analyses the determinants of changes in S-C-P over time for the food manufacturing industry in Malaysia, which is divided into five selected subindustries. The data used in this study are based on secondary data collected from various firms registered under the Company Commission of Malaysia. This study covers a period of 10 years, i.e. from 1992 to 2002. Concentration Ratio and Herfindahl-Hirschman Index and Gini Coefficient are used to measure the market structure. Meanwhile, the market conduct is measured by Advertising-Sales Ratio, whilst, the Profitability Ratio Analysis and Sales Ratio are used to measure market performance. Regression analysis using Two-Stage Least-Square is carried out to study the S-C-P model. The results indicate that the Malaysian food manufacturing industry tended to have low concentrated market throughout the study period. Nevertheless, the findings also show the industry was still characterised with oligopolistic practices which was evident by the existence of a few large firms. The advertising and rate of return also fluctuated slightly due to the influence of market elements. The results of regression analysis prove the existence of primary and feedback effects between market structure, conduct and performance based on industrial organisation approach in Malaysian food manufacturing industry. The main findings of this study are concentration do depend on firm profitability as well as advertising intensity; concentration do determine advertising; however, advertising seems to have no effect on profitability. In addition, advertisement intensity and profitability demonstrate the feedback effect; effect of conduct on structure; and performance on conduct and market structure. The relationship between concentration and advertising shows that concentrated industry spends more on advertising. Thus, higher profits also lead to higher advertising.